THE FORESIGHT OF NATIONAL ECONOMY’S DIGITAL DEVELOPMENT - Kvitka, Sergiy; Borodin, Yevgeniy; Yemelyanov, yVolodymr; Ivashova, Lіudmyla; Bohachov, Oleksii (Revista Inclusiones, 2020)
The article is devoted to the study of digital society’s development in developing economy, on the example of Ukraine. The aim of the article is to research the real situation and to identify further ways of digital development in Ukraine as a developing economy, on the basis of the Foresight technology and opportunities of the Foresight technology to optimize the interaction of public authorities with business and civil society in the digital society. The scientific originality of the article is in the fact that the opportunities of the Foresight use for analyzing and estimating the digital development in conditions of social transformation have been identified. The practical significance of the article is that specific mechanisms and methods for the implementation of the Foresight projects, which can be applied in Ukraine at the regional level, have been determined. The identification of main priorities for the development of digital society in Dnipropetrovsk region of Ukraine became the result of the study.